The Role Of Artificial Intelligence Integration And Organizational Dynamics On Optimizing Supply Chain Performance. - Ababou, Mariame (Journal of Namibian Studies, 2024)
This systematic review explores the role of artificial intelligence (AI) and organizational dynamics in optimizing supply chain management (SCM). Analyzing a series of articles published between 2010 and 2024, we identify several key findings. First, we find that AI has a positive impact on SCM operational efficiency by enabling task automation, real-time optimization and proactive risk management. Secondly, we highlight the importance of organizational factors such as management support, innovation culture and change management in the process of successful AI adoption. Despite challenges related to data confidentiality and skills gaps, AI integration offers significant opportunities for process optimization and improved decision-making in SCM. Finally, we discuss emerging trends such as the convergence of AI with other technologies and emphasize the importance of a holistic approach to fully leverage the potential of AI in SCM.